Analisis Perilaku Penggunaan Mobile Payment Aplikasi OVO menggunakan Technology Acceptance Model (TAM) Termodifikasi - Ernita Oktiviana Safitri; Yusi Tyroni Mustiyo; Niken Hendrakusma Wardhani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile Payment is an electronic financial system based on mobile devices. One of them is OVO. The advantage of OVO mobile payment is that it gives users the opportunity to collect points at various merchants. The purpose of this study is to determine the behavior of the use of OVO on user influence. Some of the variables used are perceived compability, perceived ease of use, perceived usefulness, perceived security, individual mobility, subjective norm and intention to use. Data collection techniques use questionnaires distributed online. This study also uses a population that is all obo users which is known from the results of users who have downloaded the OVO application. Respondents received a number of 100 which can be expected to be able to improve the accuracy of the money generated data. While the results of this study obtained perceived compability which did not significantly influence the behavior of OVO users with a calculated t value greater than the t table value of 1.294. While the variables that are percived ease to use, percived usefulness, percived immediately, individul mobility, subjective norm and attitude towards had significaant effect on intention to use because t count is smaller than t table.